1976
DOI: 10.1115/1.3423921
|View full text |Cite
|
Sign up to set email alerts
|

Elastostatics and Kinetics of Anisotropic and Heterogeneous Shell-Type Structures

Abstract: The authors make no attempt to summarize the results available in this area through approximate solutions of various kinds to the 3-D field equations. Nor do they present, for readers prepared to utilize modern computer techniques, finite element, boundary integral, and other numerical techniques for obtaining such solutions. Finally, it seems to the reviewer that there is little added to this book by an "Introductory Chapter" of approximately 40 pages, authored by Sih, on the "strain-energy-density factor" th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
136
0

Year Published

1982
1982
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(137 citation statements)
references
References 0 publications
1
136
0
Order By: Relevance
“…By identifying the coefficients of the same powers in (13) and (20), the following relationship between and results:…”
Section: Preliminariesmentioning
confidence: 99%
See 1 more Smart Citation
“…By identifying the coefficients of the same powers in (13) and (20), the following relationship between and results:…”
Section: Preliminariesmentioning
confidence: 99%
“…(i) in the monograph [19], the general theory of shells as substantiated in the framework of the Cosserat continuum concept furnishes valuable results for the high-order shell (and plate) theories, as well, and (ii) a large part of the monograph [20] deals with the substantiation of the high-order shell (and plate) theories, treated both in linear and nonlinear formulations. compatibility equations (C.E.)…”
mentioning
confidence: 99%
“…The refined linear theory of elastic shells with an additional account of transverse shear deformations, here called of the TimoshenkoReissner type, was extensively treated for example by Naghdi [8], Librescu [9], Pelekh [10], or Reddy [11]. Almost all linear versions of shell theory are based on various approximations in kinematical description of linear elasticity following from a through-the-thickness polynomial expansion with truncation at some level, asymptotic analyses, applying kinematic constraints etc., see Fig.…”
Section: Introductionmentioning
confidence: 99%
“…It was recognized that geometrical non-linearities due to moderate plate deflection (mainly mid-plane stretching forces) represented following the Von Kármán large deflection plate theory combined with the linear piston theory, one of the popular unsteady aerodynamic theories used, can play an important role in panel flutter [8]. This led to a number of studies [9][10][11][12][13][14][15][16] which showed that, when geometrically nonlinearities are included in the model, the linear stability boundary can be exceeded, thereby inducing stable LCO with finite amplitudes, having an order of magnitude equal to the thickness of the panel. Librescu et al [66][67][68] presented the analytical results of simply supported single-layer and three-layer flat and curved panels made from transversely isotropic materials.…”
Section: Introductionmentioning
confidence: 99%
“…These panels are subjected to in-plane loads and normal aerodynamic loads, and it is well known that unstable oscillatory motions of the panels can be caused by the coupling of elastic, inertia, and acting aerodynamic forces. This phenomenon is known as "panel flutter" [4,[9][10][11]. Dynamic aeroelastic instabilities, such as the panel flutter, are of great concern for aerospace designers, since these instabilities can lead to immediate failure or long-term fatigue failure.…”
Section: Introductionmentioning
confidence: 99%